ANALISIS HIGH-PRESSURE PROCESSING PADA PRODUK DAGING RTE: TINJAUAN TERHADAP STRUKTUR PROTEIN MIOFIBRIL DAN WHC - Aulia Alfianti (Jurnal Agroindustri Pangan, 2026)
Ready-to-eat (RTE) meat products are widely consumed due to their convenience and high nutritional value, but their high moisture and nutrient content make them prone to microbial spoilage and quality deterioration. High Pressure Processing (HPP) is a non-thermal technology that improves microbiological safety without significantly affecting sensory and nutritional quality. This review analyzes the effects of HPP on myofibrillar protein structure and its implications for water holding capacity (WHC) in RTE meat products, based on peer-reviewed articles published between 2015 and 2025 from major scientific databases. HPP modifies protein structure at secondary to quaternary levels through non-covalent interactions without altering the primary structure. Moderate pressure (100–200 MPa) induces partial unfolding, enhancing solubility, exposing reactive groups, and strengthening protein interactions, resulting in a more compact gel network and improved WHC. High pressure causes excessive denaturation and aggregation, leading to a coarse structure and reduced water retention. Optimization of pressure level and treatment duration is essential to control protein conformational changes and achieve optimal gel structure and WHC in RTE meat products.